2022
DOI: 10.1002/pip.3656
|View full text |Cite
|
Sign up to set email alerts
|

2‐step process for 5.4% CuGaSe2 solar cell using fluorine doped tin oxide transparent back contacts

Abstract: As single‐junction solar cells are approaching theoretical limits, multijunction solar cells are becoming increasingly relevant, and low‐cost wider bandgap light harvesters in tandem with silicon are the next frontier in thin film photovoltaic research. Cu‐based chalcogenide compounds have achieved great success as standard absorbers, but performance for bandgaps above 1.5 eV is still lacking. Additionally, the use of transparent back contacts remains challenging for this class of materials. In this work, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This material family is relevant in many fields, including non-linear optical, optoelectronic, and photovoltaic devices. [1][2][3] Accurate knowledge of these materials is crucial for many applications. Despite the considerable research on these materials, this knowledge is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…This material family is relevant in many fields, including non-linear optical, optoelectronic, and photovoltaic devices. [1][2][3] Accurate knowledge of these materials is crucial for many applications. Despite the considerable research on these materials, this knowledge is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the highest efficiencies of CuGaSe 2 solar cells on TBCs are much lower, at about 5%. [23][24][25][26] Recently, research on the topic of TBCs has intensified and significant progress was observed, lifting the efficiency (η) of chalcopyrite solar cells with TBCs close to the level of those with standard Mo back contacts. [27][28][29][30][31][32][33] Thus, further improvements may be expected in the near future.…”
mentioning
confidence: 99%
“…So far, the highest efficiencies of CuGaSe 2 solar cells on TBCs are much lower, at about 5%. [23][24][25][26] Recently, research on the topic of TBCs has intensified and significant progress was observed, lifting the efficiency (η) of chalcopyrite solar cells with TBCs close to the level of those with standard Mo back contacts. [27][28][29][30][31][32][33] Thus, further improvements may be expected in the near future.The best V OC values for CdS-buffered samples are achieved after a postannealing at 200 °C, reaching 971 mV for a polycrystalline [34] and 946 mV for a single-crystal absorber.…”
mentioning
confidence: 99%